Old Software, New Purpose: Exploring PPT for Interactive Language Learning - Maria Ivone, Francisca (KnE Social Sciences, 2017)
Microsoft PowerPoint (PPT) has frequently been used in language classes to present texts, pictures, animation, audio, and videos. The presentation software is extremely popular because it is available in most computers, easy to use, and supports multimedia. Yet it is seldom used to create instructional materials and media that allow language learners to be active and that encourage them to be more independent learners. The paper aims to stimulate language teachers to scrutinise the software to rediscover its potentials for language learning. The features provided in PPT allow language learners to explore, provide and record responses, and to receive feedback while they are in slideshow mode. In this paper, four PPT features – animations, ActiveX, hyperlinks, and pointer options – are explored in atypical manners and examples of language learning activities are presented to give language teachers ideas of what this old software can do to support language teaching and learning. Keywords: interactive activities, Microsoft PowerPoint (PPT), multimedia, animations, ActiveX, hyperlinks, pointer options